Industrial Electronics and Instrumentation : for engineering students - Kumar, Sunil (New Dehli : S.K. Katara & Sons, 2016)
'Industrial Electricity and Motor Controls' is a complete guide to electrical field and its equipment, including troubleshooting and repair. Electricity and electronics are introduced, thoroughly explained, and used to analyse and solve problems common to industrial electrical equipment such as motors and controls.
Thyristors -- Heat Sinks -- Applications of Thyristors -- Controlled Rectifiers -- AC Phase Control -- Applications of Phase Controlled Rectification and AC -- Phase Control Circuits -- AC Phase and Control Circuits -- Inverters -- Induction and Dielectric Heating -- Introduction to Instrumentation -- Transducers -- Signal Conditioners -- Output Devices and Displays -- Subject Review Questions -- Solution to Numerical Problems -- Experiments -- Previous Examination Questions Papers -- Index
Includes index
Keywords: Electric machinery; Industrial electronics; Electric motors -- Electronic control